THE IMPOLITENESS IN THE CHARLIE PIPPIN: A PRAGMATIC STUDY - Waliyadin Waliyadin (Vision: Journal for Language and Foreign Language Learning, 2016)
The conﬂict because of impoliteness in using language hap- pens recently in the school and family context. The case encourages the researcher to investigate the phenomena of impoliteness in communication. The types of impoliteness and the strategies used by a person in producing impolite utterance are investigated. Due to the lack of data sources depicted the conﬂict in the school and family naturally, the novel Charlie Pippin by Candy Dawson Boyd (1987) is used as the data sources. Culpeper’s models of super strategies impoliteness (1996, 2005) are used as the theoretical framework. The ﬁnding shows that each character in the novel used different strategy of impoliteness according to their social level. The character has high social level often used bald on record impoliteness and positive impoliteness. This research support the previous research conducted by Mohammed (2016).